Sources of Volatility during Four Oil Price Crashes - Baffes, John; Kshirsagar, Varun (World Bank, Washington, DC, 2015)
Previous sharp oil price declines have been accompanied by elevated ex post volatility. In contrast, volatility was much less elevated during the oil price crash in 2014/15. This paper provides evidence that oil prices declined in a relatively measured manner during 2014/15, with dispersion of price changes that was considerably smaller than comparable oil price declines. This finding is robust to nonparametric and GARCH measures of volatility. Further, the U.S. dollar appreciation exerted a strong influence on volatility during the recent crash; in contrast, the impact of shocks on equity markets was muted.